Um Conto De Duas Cidades: Diálogo Arquitetônico Entre Braga E Diamantina Do Século Xviii - Oliveira, Henrique Goncalves [UNIFESP] (2018)
Diamantina And Braga Are Two Cities Of Gigantic Architectural Beauty. During The Eighteenth Century, The History Of The Two Cities Intersected. This Work Presents A Study That Goes Through Various Definitions Of City And City Types To Demonstrate That On The Basis Of These Definitions It Is Possible To Find Similarities And Dissimilarities That Foster A Dialogue With Visual Bases On The Architectural Production Of This Period In Both Cities.